Exosomal Long Non-coding RNA HOTTIP Increases Resistance of Colorectal Cancer Cells to Mitomycin via Impairing MiR-214-Mediated Degradation of KPNA3 - Chen, Xijuan; Liu, Yingqiang; Zhang, Qinglan; Liu, Baoxing; Cheng, Yan; Zhang, Yonglei; Sun, Yanan; Liu, Junqi; Gen, Hong (Frontiers in Cell and Developmental Biology, 2021)
It has been reported that long noncoding RNA HOXA distal transcript antisense RNA (lncRNA HOTTIP) functions as a tumor promoter in colorectal cancer (CRC). Hence, we paid attention to exploring whether exosomes could carry lncRNA HOTTIP to affect the mitomycin resistance in CRC and to identify the underlying mechanisms. High expression of HOTTIP was detected in mitomycin-resistant CRC cells. Inhibition of HOTTIP reduced the mitomycin resistance. In the co-culture system of mitomycin-resistant cells or their derived exosomes with CRC cells, the HOTTIP was found to be transferred into the parental cells via extracellular vesicles (EVs) secreted from mitomycin-resistant cells and to contribute to the mitomycin resistance. Based on the bioinformatics databases, possible interaction network of HOTTIP, microRNA-214 (miR-214) and Karyopherin subunit alpha 3 (KPNA3) in CRC was predicted, which was further analyzed by dual-luciferase reporter, RNA binding protein immunoprecipitation and RNA pull-down assays. As HOTTIP down-regulated miR-214 to elevate the KPNA3 expression, HOTTIP enhanced the mitomycin resistance through impairing miR-214-dependent inhibition of KPNA3. Finally, HOTTIP was suggested as an independent factor predicting mitomycin response in patients with CRC. Those data together confirmed the promotive effects of EV-carried HOTTIP on the mitomycin resistance, while targeting HOTTIP might be a promising strategy overcoming drug resistance in CRC.